The Sweet Drive Test: refining phenotypic characterization of anhedonic behavior in rodents - Mateus-Pinheiro, António; Patricio, Patricia; Alves, Nuno D.; Machado-Santos, Ana R.; Morais, Monica; Bessa, João M.; Sousa, Nuno; Pinto, Luisa (Frontiers in Behavioral Neuroscience, 2014)
Measuring anhedonic behavior in rodents is a challenging task as current methods display only moderate sensitivity to detect anhedonic phenotype and, consequently, results from different labs are frequently incongruent. Herein we present a newly-developed test, the Sweet Drive Test (SDT), which integrates food preference measurement in a non-aversive environment, with ultrasonic vocalizations (USVs) recording. Animals were placed in a soundproofed black arena, under red light illumination, and allowed to choose between regular and sweet food pellets. During the test trials, 50 KHz ultrasonic vocalizations, previously described to be associated with positive experiences, were recorded. In a first experimental approach, we demonstrate the ability of SDT to accurately characterize anhedonic behavior in animals chronically exposed to stress. In a subsequent set of experiments, we show that this paradigm has high sensitivity to detect mood-improving effects of antidepressants. The combined analysis of both food preference and the number of 50 KHz vocalizations in the SDT provides also a valuable tool to discriminate animals that responded to treatment from non-responder animals.